PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BILINGUAL TIPE PARTIAL IMMERSION DENGAN SETING PEMBELAJARAN KOOPERATIF TIPE STAD - Wiratini, Ni Putu Ari; Suparta, I Nengah; Sadra, I Wayan (Jurnal Pendidikan Matematika, 2013)
Abstrak Penelitian ini merupakan penelitian pengembangan yang bertujuan untuk mengembangkan perangkat pembelajaran matematika bilingual dengan seting pembelajaran kooperatif tipe STAD bagi siswa SMA kelas X. Perangkat pembelajaran yang dikembangkan berupa buku siswa, dan buku petunjuk guru. Pengembangan perangkat tersebut mengikuti prosedur dari Plomp yang mengandung lima tahap yaitu: (1) investigasi awal; (2) desain; (3) realisasi; (4) tes, evaluasi, dan revisi; dan (5) implementasi. Pada penelitian ini tahap implementasi tidak dilaksanakan karena keterbatasan peneliti. Perangkat yang dikembangkan sudah memiliki kualitas yang baik, karena telah memenuhi tiga aspek; validitas, kepraktisan, dan keefektivan. Skor validitas perangkat pembelajaran berupa buku siswa adalah 3,63 dan skor validitas buku petunjuk guru 3,77. Skor buku siswa dan buku petunjuk guru termasuk dalam interval 3,5â¤Sr<4,0 sehingga berkatagori sangat valid. Kepraktisan perangkat pembelajaran dianalisisÂ melalui skor pengamatan keterlaksaan perangkat pembelajaran, respons guru, dan respons siswa. Skor pengamatan keterlaksanaan pembelajaran siklus I adalah 3,29Â masuk dalam interval 2,5â¤Sr<3,5 sehingga masuk dalam katagori praktis. Pada siklus II dan III, skor pengamatan keterlaksanaan pembelajaran adalah 3,61 dan 3,83 yang masuk dalam interval 3,5â¤Sr<4,0 sehingga berkatagori sangat praktis. Skor respons guru adalah 3,65 masuk dalam interval 3,5â¤Sr<4,0 sehingga berkatagori sangat praktis.Skor respons siswa adalah 3,44 masuk dalam interval 2,5â¤Sr<3,5 sehingga berkatagori praktis. EfektivitasÂ perangkat pembelajaran dianalisis dari hasil belajar siswa yaitu ranah kognitif dan afektif. Skor hasil belajar siswa ranah kognitif siklus I adalah 83,2, siklus II 86,13, dan siklus III 88,83. Skor afektif siswa termasuk dalam katagori efektif. Â Kata kunci: kooperatif, STAD, bilingual Â Abstract This research was a developmental research which was aimed at developing bilingual mathematics teaching-learning instrumentsÂ based on STAD cooperative learning setting for grade X senior high school students. In this study the studentsâ handbooks and teacherâs instructional guides were developed following Plompâs developmental procedure which consists of five stages: (1) preliminary investigation, (2) design, (3) realization, (4) test, evaluation, and revision, and (5) implementation.Â In this study the implementation stage was not involved because of the research limitations. According to research findings the instruments which had been developed have good quality based on the consideration ofÂ three aspects: validity, practicality, and effectiveness. The validity score of studentsâ handbook was 3,63 and the one ofÂ teacherâs instructional guide was 3,77. These scores were in the range of 3,5â¤Sr<4, showing that studentsâ and teacherâs handbooks were very valid. The practical aspect of instruments was analysed using teaching-learning observations, teacherâs response and studentsâ response. The observations average score of using those instrument in the first learning cycle was 3,29 which wasÂ in the range of 2,5â¤Sr<3,5.Â This showed that the practical aspect of using instruments was in practise catagory. In the second and third cycles, the observationsâ average scores of the teaching learning process wereÂ 3,61 and 3,83 which both were in the range of 3,5â¤Sr<4,0. These indicated that the practical aspect of instruments were very practicable. The score of teacherâs response was 3,65 which was in the range of 3,5â¤Sr<4,0. This indicates that the practical aspect of instruments was very practicable. The score of studentsâ response was 3,44 which was in the range of 2,5â¤Sr<3,5 showing that practical aspect ofÂ instruments was in practise catagory. Morever, instruments effectiveness was measured using students achievement in cognitive and affective domain. The score of students achievement in the cognitive domain in the first cycle was 83,2, the second cycle was 86,13, and in the third cycle was 88,83. The students score in affective domain was effective. Â Keywords : cooperative, STAD, bilingual